KUALITAS PELAYANAN PUBLIK BIDANG ADMINISTRASI KEPENDUDUKAN DI DESA TAMBAKSARI KECAMATAN PURWODADI KABUPATEN PASURUAN - Muhammad Saifuloh; Nur Lailul Fitrotin (Journal Publicuho, 2021)
This study aims to determine the quality of public services in the field of population administration in Tambaksari Village. This study uses a qualitative approach with observation, interview, and documentation techniques. The results of the study were measured based on the quality of services in Tambaksari Village. It can be seen by several factors that influence it.The results showed that the quality of public services carried out in population administration services in Tambaksari Village, Purwodadi District, Pasuruan Regency has not been implemented optimally, due to the lack of supporting facilities and other resources in the service process in the field of population administration